Szaleństwo i literatura. O Dziennikach Stefana Żeromskiego w perspektywie afektywnej - Chyła, Karolina (Przestrzenie Teorii, 2021)
Using the tools offered by affect theory, this article aims to present the theme of madness, its numerous incarnations and transformations in the text of the diaries that Stefan Żeromski left behind. Madness is depicted here as a phenomenon defying any kind of unambiguity; it can be anything from a secret of nature to be deciphered, through a creative frenzy of inspiration, to a state of apathy, sometimes interwoven with sudden ecstasy, triggered by the chronic hunger that Żeromski suffered as a young man, in other words: during his diarist period.